Societal impact of the Heroine’s Learning Journey: Inspiring women in STEM through the power of role models - Luis Felipe Coimbra Costa; Carlos Eduardo Barbosa; Luciana Maria Azevedo Nascimento; Larissa Galeno; Yuri Lima; Ana Moura Santos; Geraldo Xexéo; Jano Moreira de Souza (Societal Impacts)
The Heroine’s Learning Journey (HLJ) is an educational framework addressing gender disparities in STEM. Supported by the FOSTWOM project, it motivates young women through innovative practices and international collaboration. Drawing on heroic narratives from Campbell’s Hero’s Journey and Murdock’s Heroine’s Journey, HLJ integrates these stories with the Heroines Learning System (HeLaS), a digital platform for scalable and adaptable learning environments. This model aims to enhance female participation in STEM courses and assess the societal impact of HLJ. The Heroine’s Learning Journey has been implemented in educational settings, including online courses and a case study in the rural community of Recreio, Brazil. We collected quantitative and qualitative data to evaluate the model’s effectiveness. The results demonstrate the HLJ’s potential to inspire systemic change by fostering a more inclusive and diverse STEM landscape. This research highlights the importance of innovative educational approaches in driving societal transformation and shaping the future of STEM education.